PERBANDINGAN PENERAPAN TINDAKAN PENYADAPAN OLEH PENEGAK HUKUM DALAM PENYIDIKAN TINDAK PIDANA KORUPSI - Hakim Panca Putra (2023)
Wiretapping is an act that violates human rights, especially the right to privacy. Even though it violates human rights, wiretapping can still be carried out by law enforcement officials in the criminal justice process to seek evidence from a criminal case. However, the existing regulations have several differences in the application of wiretapping between the Corruption Eradication Commission and the Police or the Attorney General's Office. Based on this, the authors conducted a study aimed at comparing the implementation of wiretapping in Indonesia and exploring whether wiretapping arrangements should be integrated into one law. The author uses a normative juridical research method where the writer uses literature studies and interviews as data sources. The results of research conducted by the author explain that in Indonesia, regulations regarding wiretapping are widely scattered in various laws and regulations. However, the current regulations do not yet regulate the application of wiretapping in a comprehensive manner, so that existing regulations can still be abused by law enforcement officials. The existing application of wiretapping also has an imbalance between law enforcement agencies, causing several problems. Therefore, the author is of the opinion that the regulation regarding wiretapping must be renewed so that it can provide legal certainty. There are two things that can be done regarding the reform regarding the application of wiretapping by law enforcement, namely the reform of the Criminal Procedure Code and the drafting of a law regarding wiretapping.